2015
DOI: 10.3109/00207454.2014.990559
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR C677T mutation increased the risk of Ischemic Stroke, especially in large-artery atherosclerosis in adults: an updated meta-analysis from 38 researches

Abstract: This meta-analysis suggests that MTHFR C677T mutation increased the risk of Ischemic Stroke in adults, especially in large-artery atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
4
9
0
1
Order By: Relevance
“…Associations between MTHFR gene C677T and ACE I/D polymorphism and ischemic stroke have been reported in several studies . The recent results of meta‐analyses suggested that the C667T mutation was significantly associated with increased risk of ischemic stroke in adults, especially in large‐artery atherosclerosis . These results were confirmed in our study with 5/24 patients with TT and 10/24 with CT genotype and an overall mutated T allele frequency of 41.7%.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Associations between MTHFR gene C677T and ACE I/D polymorphism and ischemic stroke have been reported in several studies . The recent results of meta‐analyses suggested that the C667T mutation was significantly associated with increased risk of ischemic stroke in adults, especially in large‐artery atherosclerosis . These results were confirmed in our study with 5/24 patients with TT and 10/24 with CT genotype and an overall mutated T allele frequency of 41.7%.…”
Section: Discussionsupporting
confidence: 88%
“…29,31 The recent results of meta-analyses suggested that the C667T mutation was significantly associated with increased risk of ischemic stroke in adults, especially in large-artery atherosclerosis. 32,33 These results were confirmed in our study with 5/24 patients with TT and 10/24…”
Section: Genotypingsupporting
confidence: 88%
“…Oral contraception is also a preponderant risk factor between the young subjects; these results can be Genetically speaking, studies have suggested that MTHFR C677T variant could be a determining event of atherothrombotic IS in Morocco, which is perfectly in line with the results reported in a recent meta-analysis showing that the MTHFR C677T mutation increased the risk of IS in adulthood, particularly in atherosclerosis of large arteries [60]. The study by Diakite et al (2014) suggested a statistically significant association between G894T polymorphism of eNOS gene and IS, which is consistent with the results of a meta-analysis confirming that G894T polymorphism of eNOS gene is associated with high risk of IS among Asian populations [61].…”
Section: The Percentage Of Patients With Thrombolyzed Ischemic Strokesupporting
confidence: 86%
“…[5][6][7][8][9] For example, clinical studies show that atherosclerosis is closely associated with the development of stroke. [10][11][12] Individuals with risk factors for atherosclerosis, such as hypertension, hypercholesterolemia, and obesity, more often develop ischemic stroke. 9 Renal dysfunction is another proposed risk factor for cardiovascular events in patients with atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%